Effects of paraoxonase 1 on the cytodifferentiation and mineralization of periodontal ligament cells. (24th October 2017) - Masumoto, R.; Kitagaki, J.; Matsumoto, M.; Miyauchi, S.; Fujihara, C.; Yamashita, M.; Yamada, S.; Kitamura, M.; Murakami, S.
Abstract : Background and Objective: Single nucleotide polymorphisms (SNPs) of paraoxonase 1 (PON1) are known to be associated with the pathogenesis of osteoporosis and periodontitis. However, the effects of PON1 on the osteoblastic differentiation of periodontal ligament (PDL) cells are unclear. In this study, we examined the effects of PON1 on the osteoblastic differentiation of PDL cells, and analysed the role of PON1 SNPs on the pathogenesis of aggressive periodontitis (AgP) in the Japanese population. Material and Methods: Human PDL (HPDL) cells were exposed to the PON1 plasmid and PON1 inhibitor, 2‐hydroxyquinoline, and cultured in mineralization medium. Expression of calcification‐related genes and calcified nodule formation were assessed by real‐time PCR, an alkaline phosphatase (ALPase) activity assay and Alizarin red staining. Sanger sequencing was performed to evaluate whether PON1 SNPs are associated with the pathogenesis of AgP in Japanese people. Results: During osteoblastic differentiation of HPDL cells, expression of PON1 mRNA increased in a time‐dependent manner. PON1 stimulated an increase in expression of mRNA for calcification‐related genes, as well as ALPase activity. In contrast, 2‐hydroxyquinoline clearly inhibited the expression of calcification‐related genes, ALPase activity and calcified nodule formation in HPDL cells. Moreover, there was a statistically significant difference in the minor allele frequency of PON1 SNP rs854560 between the Japanese control database and patients with AgP in the Japanese population ( P  = .0190). Conclusion: PON1 induced cytodifferentiation and mineralization of HPDL cells, and PON1 SNP rs854560 may be associated with the pathogenesis of AgP in the Japanese population.